The implementation of a collaborative action research programme for developing inclusive practices: Social learning in small internal networks - Angelides, Panayiotis; Georgiou, Renos; Kyriakou, Kyriaki (My University, 2008)
The idea of inclusive education has featured very highly in the educational priorities of many educational systems. However, the same educational systems are very often criticised because of the difficulties of their teachers to respond to inclusive environments of learning, where all children, despite their abilities, receive equal opportunities in teaching and learning. In this study, we implement a programme of collaborative action research with the purpose of investigating the degree to which it could contribute to the development of inclusive practices. The research reported here took place in a primary school classroom in Cyprus. Our findings from this research shed further light on the nature of differentiation in the preparation and teaching of teachers in relation to inclusive education as well as on the role of teachers as leaders in this process. The collaborative process was successful because it supported experimentation and reflection and provided to all involved opportunities to consider new possibilities. Our experience from this process suggests that if we are interested in developing such practices we cannot follow simple formulas. Rather what we need is a system of social learning within the workplace that builds on existing conditions. Inclusive practices in Cyprus schools, then, should not be approached as simplistic recipes or trite formulas but as social learning that will be developed in small networks and communities of practice.
Keywords: Collaborative action research; Collaborative inquiry; Cyprus education; Inclusive education; Inclusive practices